MODERASI BERAGAMA BERBASIS MASJID: ANALISIS KONTEN KANAL YOUTUBE-TV MASJID ISTIQLAL JAKARTA - Vitara Ridesta; Nazwa Aulia; Atik Hajar Zaidah; Nanik Puji Hastuti; Maryunah Maryunah; Fakhrurozi Fakhrurozi (Academic Journal of Islamic Principles and Philosophy, 2022)
This study aims to prevent and overcome the rising trend of radical extremism in Indonesia. Channel Youtube becomes one of the most effective alternative tools for spreading moderate Islamic ideas in the digital era. This study uses a qualitative approach, wherein the data are obtained through interviews, observations, and content analysis of the Istiqlal Mosque Jakarta Youtube-TV channel. The study results show that the Youtube channel used by the management of the Istiqlal mosque in Jakarta has become an effective medium for spreading the values of Islam wasathiyyah. The existing contents of the channel are in accordance with the indicators of religious moderation, namely commitment to nationalism, tolerance, anti-violence, and accommodating to the local wisdom. In addition, the channel has been widely watched and even become one of the public references for religious moderation knowledge in the digital era.